Twin recrystallization mechanisms in magnesium-rare earth alloys. (1st September 2015) - Basu, I.; Al-Samman, T.
Graphical abstract: Abstract: Binary Mg-1 wt.% Gd and Mg-1 wt.% Ce wrought alloys, with basal type starting texture, are subjected to plane strain compression. Specially oriented specimens invoking c -axis extension (In Plane Compression) and c -axis compression (through thickness compression) were deformed to 6% and 13% respectively. Deformation in Mg-1Gd under in plane compression (IPC) led to evolution of sharp 'prismatic fiber' texture, whereas a weak basal texture was witnessed for Mg-1Ce. In case of through thickness compression (TTC), Mg-1Gd gave rise to a split basal component, whereas Mg-1Ce resulted in a weak basal component with large off-basal spread. Microstructurally, Mg-1Gd displayed unequivocal activation of both 1 0 1 ¯ 2 tension twinning and 1 0 1 ¯ 1 compression twinning during IPC, while profuse 1 0 1 ¯ 1 compression twinning for the TTC mode. Majority of the compression twins underwent second generation 1 0 1 ¯ 2 tension twinning to give rise to 1 0 1 ¯ 1 – 1 0 1 ¯ 2 double twins. Compression and double twinned regions showed strong slip activity leading to the formation of fine recovered sub-structure. On the contrary, Mg-1Ce exhibited a conventional deformation response with twinning being predominantly of 1 0 1 ¯ 2 tension type. Annealing led to preservation of the deformation texture components along with strong texture weakening. Recrystallization in Mg-1Gd commenced discontinuously in compression and double twins, which at higher temperatures showed favorable growth behavior consuming the still deformed matrix and tension twins. Mg-1Ce displayed continuous recrystallization marked by recovery and growth of orientationally soft tension twins along with nucleation in the vicinity of particles.